Identification of Cross-Pathway Connections via Protein-Protein Interactions Linked to Altered States of Metabolic Enzymes in Cervical Cancer - Kumar, Krishna; Bose, Sarpita; Chakrabarti, Saikat (Frontiers in Medicine, 2021)
Metabolic reprogramming is one of the emerging hallmarks of cancer cells. Various factors such as signaling proteins, miRNA, transcription factors, etc. may play important roles in altering the metabolic status in cancer cells by interacting with metabolic enzymes either directly or via protein-protein interactions. Therefore, it is important to understand the coordination among these cellular pathways, which may provide better insight into the molecular mechanism behind metabolic adaptations in cancer cells. Here, we have designed a cervical cancer-specific supra-interaction network where signaling pathway proteins, transcription factors, and microRNAs are connected to metabolic enzymes via protein-protein interactions to investigate novel molecular targets and connections/links/paths regulating the metabolic enzymes. Using publicly available omics data and protein-protein interactions, we developed a Hidden Markov Model (HMM) based mathematical model yielding 94, 236, and 27 probable links/paths connecting signaling pathway proteins, transcription factors, and miRNAs to metabolic enzymes, respectively out of which 83 paths connect to 6 common metabolic enzymes (RRM2, NDUFA11, ENO2, EZH2, AKR1C2, and TYMS). Signaling proteins (e.g., PPARD, BAD, GNB5, CHECK1, PAK2, PLK1, BRCA1, MAML3, and SPP1), transcription factors (e.g., KAT2B, ING1, MED1, ZEB1, AR, NCOA2, EGR1, TWIST1, E2F1, ID4, RBL1, ESR1, and HSF2) and microRNA (e.g., mir-147a, mir-593-5p, mir-138-5p, mir-16-5p, and mir-15b-5p) were found to regulate 2 key metabolic enzymes, EZH2 and AKR1C2 with altered metabolites (L-lysine and Tetrahydrodeoxycorticosterone) status in cervical cancer. We believe, our systems biology-based approach will pave the way for future studies which could be aimed towards identifying novel signaling, transcriptional, and post-transcriptional regulators of metabolic alterations in cervical cancer.